The medical file: an instrument for work and study, legal proof - Candia, Luigi; Cambieri, Andrea (Medicina e Morale, 1991)
The medical file is a customary instrument of work for the hospital physician but it is not adequately recognized from the point of view of its doctrine and applications. In this paper it is therefore examined from the point of view of the correct gathering of medical information, the scientific-didactic meaning and the medical-legal implications, in an attempt to summarize the most relevant elements that the correct "management" implies for the physician and for the hospital.